Method for preparing Al2O3 / Al ceramic metal coating with porous structure on surface of aluminum-based composite material

The porous alumina ceramic coating is prepared by using microarc oxidation technology on the surface of aluminum-based composite materials, and the Al2O3/Al ceramic metal coating is formed through high-temperature penetration, which solves the complex preparation method of ceramic-metal composite materials and the insufficient thermal conductivity regulation. The problem of this problem has achieved excellent mechanical properties and high thermal conductivity, and is suitable for applications in a variety of harsh environments.

CN119287476AActive Publication Date: 2025-01-10HARBIN INST OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411452420.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-10
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

The existing ceramic-metal composite preparation methods are complex, uncontrollable, high cost, and difficult to balance strength and toughness, and insufficient thermal conductivity regulation, especially in preparing multi-layers composed of metal-based composite materials and ceramic-metal composite coatings. There is a lack of effective methods for composite materials.

Method used

Microarc oxidation technology is used to prepare a porous alumina ceramic coating on the surface of aluminum-based composite materials, and the Al2O3/Al ceramic metal coating is formed through high-temperature penetration to form a multi-layer structural composite material, and the porous structure is used to achieve aluminum penetration and the filling of the ceramic layer, forming a coating with excellent mechanical properties and high thermal conductivity.

Benefits of technology

Achieves high mechanical strength and high thermal conductivity in low-cost and low-temperature conditions. It is suitable for future development of packaging substrate materials and composite materials in deep-sea/deep space/deep ground harsh environments, with better resistance Friction wear, thermal shock resistance and high fracture toughness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287476A_ABST
    Figure CN119287476A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a porous structure Al2O3 / Al ceramic metal coating on the surface of an aluminum-based composite material, and belongs to the technical field of aluminum-based composite material surface treatment. The invention aims to solve the problems that a method for preparing a ceramic-metal composite material in the prior art is complex, uncontrollable and high in cost, the strength and toughness of the composite material are difficult to balance, and the thermal conductivity is insufficient to regulate and control. The method comprises the following steps: 1, pretreating the surface of the aluminum-based composite material; 2, preparing a porous micro-arc oxidation coating; and 3, preparing the Al2O3 / Al ceramic coating with a complete structure. The composite material with the multilayer structure prepared by the invention has more excellent mechanical properties (friction and wear resistance, high thermal shock resistance, adjustable thermal expansion coefficient and high fracture toughness) and high thermal conductivity (greater than or equal to 100W / mK), and has important significance for upgrading of future packaging substrate materials and development of composite materials for deep sea / deep space / deep ground severe environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface treatment of aluminum-based composite materials, and in particular relates to a method for preparing a porous Al2O3 / Al ceramic metal coating on the surface of an aluminum-based composite material. Background Art

[0002] Compared with ceramic materials, metals usually show better ductility and fracture toughness, among which aluminum alloys have outstanding specific strength and specific stiffness. However, the absolute strength, stiffness and fracture toughness of metals are all low, which limits the wide application of metals to a certain extent. With the continuous improvement of productivity development needs, single metals or single ceramics are difficult to meet the increasingly stringent working conditions of parts. Ceramic-metal composites have the advantages of multiple components, high specific strength and modulus, high fatigue strength, good fracture toughness, etc., which can achieve performance complementarity between different materials and show broad application prospects. However, the current preparation method of ceramic-metal composites is complex and uncontrollable, strength and toughness are difficult to balance, and thermal conductivity is insufficient. In addition, the survey found that there is no report on the preparation of multilayer composites composed of metal-based composites and ceramic-metal composite coatings. This multilayer structure composite material has more excellent mechanical properties (friction and wear resistance, high thermal shock resistance, adjustable thermal expansion coefficient, high fracture toughness) and high thermal conductivity (≥100W / mK), which is of great significance to the future replacement of packaging substrate materials and the development of composite materials for harsh environments in deep sea / deep space / deep earth. Summary of the invention

[0003] The purpose of the present invention is to solve the problems that the methods for preparing ceramic-metal composite materials in the prior art are complex, uncontrollable and costly, and the strength and toughness of the composite materials are difficult to balance and the thermal conductivity is insufficiently regulated, and to provide a method for preparing a porous Al2O3 / Al ceramic metal coating on the surface of an aluminum-based composite material.

[0004] A method for preparing a porous Al2O3 / Al ceramic metal coating on the surface of an aluminum-based composite material is specifically completed by the following steps:

[0005] 1. Pretreatment of the surface of aluminum-based composite materials:

[0006] Removing impurities and oil stains on the surface of the aluminum-based composite material to obtain a pretreated substrate;

[0007] 2. Preparation of porous micro-arc oxidation coating:

[0008] ①, dissolving sodium silicate, sodium aluminate, sodium phosphate and sodium hydroxide in deionized water to obtain an electrolyte;

[0009] ②, immersing the pretreated substrate into a stainless steel electrolytic cell filled with an electrolyte, connecting the pretreated substrate to the positive electrode of a power source, connecting the stainless steel electrolytic cell to the negative electrode of the power source, and micro-arc oxidation for a period of time under the conditions of an electrolyte temperature of 30°C to 50°C, an applied voltage of 400V to 600V, a frequency of 200Hz to 1000Hz, and a duty cycle of 4% to 30%, to obtain an aluminum-based composite material with an alumina ceramic coating having a porous structure;

[0010] 3. Preparation of Al2O3 / Al ceramic coating with complete structure:

[0011] The aluminum-based composite material with a porous alumina ceramic coating is placed in a high-temperature furnace, heated to 550°C-650°C, and kept at 550°C-650°C for a period of time to obtain an aluminum-based composite material with a porous Al2O3 / Al ceramic metal coating on the surface.

[0012] Principle of the present invention:

[0013] The present invention uses micro-arc oxidation technology to prepare porous alumina on the surface of pretreated aluminum-based composite materials for the following purposes: 1. Maintaining high porosity (including through holes) to provide a channel for subsequent high-temperature diffusion of aluminum in the composite material, thereby achieving diffusion of aluminum into the ceramic layer and on its surface; 2. Filling the pores well during the high-temperature diffusion of aluminum, thereby quickly forming a ceramic-metal composite material, and finally forming a multilayer composite material consisting of an Al2O3 / Al ceramic-metal outer layer + an aluminum-based composite material substrate; the multilayer composite material has more excellent mechanical properties (friction and wear resistance, high thermal shock resistance, adjustable thermal expansion coefficient, high fracture toughness) and high thermal conductivity (≥100W / mK).

[0014] Advantages of the present invention:

[0015] The present invention obtains a ceramic-metal composite coating with excellent mechanical strength / high thermal conductivity on the surface of an aluminum-based composite material at low cost and lower temperature conditions, which is of great significance to the future upgrading of packaging substrate materials and the development of composite materials for harsh deep-sea / deep-space / deep-earth environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Schematic diagram of the structure of aluminum-based composite materials with porous Al2O3 / Al ceramic metal coatings prepared in different embodiments;

[0017] Figure 2 A macroscopic image of the aluminum-based composite material having a porous Al2O3 / Al ceramic metal coating prepared in Example 1;

[0018] Figure 3The SEM image of the aluminum-based composite material with a porous Al2O3 / Al ceramic metal coating prepared in Example 1;

[0019] Figure 4 XRD pattern of the aluminum-based composite material with porous Al2O3 / Al ceramic metal coating prepared in Example 1;

[0020] Figure 5 Thermal conductivity data of aluminum-based composite materials with porous Al2O3 / Al ceramic metal coatings prepared in different embodiments;

[0021] Figure 6 The friction coefficient of the aluminum-based composite material with a porous Al2O3 / Al ceramic metal coating prepared in different embodiments;

[0022] Figure 7 Thermal expansion coefficient of aluminum-based composite materials with porous Al2O3 / Al ceramic metal coatings prepared in different embodiments;

[0023] Figure 8 The room temperature compressive strength of the aluminum-based composite material with a porous Al2O3 / Al ceramic metal coating prepared in different embodiments;

[0024] Fig. 9 The fracture toughness of the aluminum-based composite material with porous Al2O3 / Al ceramic metal coating prepared in different embodiments. DETAILED DESCRIPTION

[0025] Specific implementation method 1: This implementation method is a method for preparing a porous Al2O3 / Al ceramic metal coating on the surface of an aluminum-based composite material, which is specifically completed by the following steps:

[0026] 1. Pretreatment of the surface of aluminum-based composite materials:

[0027] Removing impurities and oil stains on the surface of the aluminum-based composite material to obtain a pretreated substrate;

[0028] 2. Preparation of porous micro-arc oxidation coating:

[0029] ①, dissolving sodium silicate, sodium aluminate, sodium phosphate and sodium hydroxide in deionized water to obtain an electrolyte;

[0030] ②, immersing the pretreated substrate into a stainless steel electrolytic cell filled with an electrolyte, connecting the pretreated substrate to the positive electrode of a power source, connecting the stainless steel electrolytic cell to the negative electrode of the power source, and micro-arc oxidation for a period of time under the conditions of an electrolyte temperature of 30°C to 50°C, an applied voltage of 400V to 600V, a frequency of 200Hz to 1000Hz, and a duty cycle of 4% to 30%, to obtain an aluminum-based composite material with an alumina ceramic coating having a porous structure;

[0031] 3. Preparation of Al2O3 / Al ceramic coating with complete structure:

[0032] The aluminum-based composite material with a porous alumina ceramic coating is placed in a high-temperature furnace, heated to 550°C-650°C, and kept at 550°C-650°C for a period of time to obtain an aluminum-based composite material with a porous Al2O3 / Al ceramic metal coating on the surface.

[0033] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the aluminum-based composite material described in step 1 is SiC-reinforced aluminum alloy, wherein the mass fraction of SiC is 10% to 50%. The other steps are the same as those in specific implementation method 1.

[0034] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the aluminum alloy described in step 1 is 2024 aluminum alloy, 6061 aluminum alloy, or 1050 aluminum alloy. The other steps are the same as those in specific implementation method 1 or 2.

[0035] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the concentration of sodium silicate in the electrolyte described in step 2① is 1 g / L to 20 g / L, the concentration of sodium aluminate is 1 g / L to 20 g / L, the concentration of sodium phosphate is 1 g / L to 40 g / L, and the concentration of sodium hydroxide is 1 g / L to 20 g / L. The other steps are the same as those of specific embodiments 1 to 3.

[0036] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the time of micro-arc oxidation in step 2② is 10 minutes to 80 minutes. The other steps are the same as those of specific embodiments 1 to 4.

[0037] Specific implementation 6: This implementation is different from specific implementations 1 to 5 in that the thickness of the porous alumina ceramic coating in step 2② is 10 μm to 100 μm and the porosity is 10% to 40%. The other steps are the same as specific implementations 1 to 5.

[0038] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the heating rate in step 3 is 5°C / min to 8°C / min. The other steps are the same as those in specific embodiments 1 to 6.

[0039] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the insulation time in step 3 is 10 minutes to 30 minutes. The other steps are the same as those in specific embodiments 1 to 7.

[0040] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: in step 3, the aluminum-based composite material with a porous alumina ceramic coating is placed in a high-temperature furnace, heated to 600° C. to 650° C., and kept at 600° C. to 650° C. for a period of time. The other steps are the same as those of specific embodiments 1 to 8.

[0041] Specific embodiment 10: The difference between this embodiment and specific embodiments 1 to 9 is that the aluminum-based composite material with a porous Al2O3 / Al ceramic coating on the surface described in step 3 has excellent mechanical properties and high thermal conductivity, excellent mechanical properties, friction coefficient <0.5, 400℃ thermal shock 500 times composite material intact, thermal expansion coefficient 5~15×10 -6 / ℃, room temperature compression and bending strength>1GPa, fracture toughness about 16~20MPa·m 1 / 2 , thermal conductivity ≥ 100 W / mK. The other steps are the same as those in the first to ninth embodiments.

[0042] The following examples are used to verify the beneficial effects of the present invention:

[0043] Example 1: A method for preparing a porous Al2O3 / Al ceramic metal coating on the surface of an aluminum-based composite material, which is specifically completed by the following steps:

[0044] 1. Pretreatment of the surface of aluminum-based composite materials:

[0045] Removing impurities and oil stains on the surface of the aluminum-based composite material to obtain a pretreated substrate;

[0046] In step 1, the surface of the aluminum-based composite material is polished using 800#, 1000# and 1200# sandpapers in sequence to remove impurities and an oxide layer on the surface, and then ultrasonically cleaned using anhydrous ethanol and deionized water for 15 minutes respectively to obtain a pretreated substrate;

[0047] The aluminum-based composite material described in step 1 is SiC reinforced 2024 aluminum alloy, wherein the mass fraction of SiC is 45%;

[0048] 2. Preparation of porous micro-arc oxidation coating:

[0049] ①, dissolving sodium silicate, sodium aluminate, sodium phosphate and sodium hydroxide in deionized water to obtain an electrolyte;

[0050] The electrolyte in step 2① has a sodium silicate concentration of 15 g / L, a sodium aluminate concentration of 10 g / L, a sodium phosphate concentration of 20 g / L, and a sodium hydroxide concentration of 5 g / L;

[0051] ②, immersing the pretreated substrate into a stainless steel electrolytic cell filled with electrolyte, connecting the pretreated substrate to the positive electrode of the power supply, connecting the stainless steel electrolytic cell to the negative electrode of the power supply, and micro-arc oxidation for 50 minutes under the conditions of electrolyte temperature of 40°C, applied voltage of 500V, frequency of 600Hz and duty cycle of 10%, to obtain an aluminum-based composite material with an alumina ceramic coating with a porous structure;

[0052] In step 2②, the thickness of the porous alumina ceramic coating is 100 μm and the porosity is 30%;

[0053] 3. Preparation of Al2O3 / Al ceramic coating with complete structure:

[0054] The aluminum-based composite material with a porous alumina ceramic coating was placed in a high-temperature furnace, heated from room temperature to 600°C at a heating rate of 5°C / min, and kept at 600°C for 20 minutes. Figure 1 As shown, an aluminum-based composite material with a porous Al2O3 / Al ceramic metal coating on the surface can be obtained, which has a dual composite material structure, the substrate is an aluminum-based composite material, and the surface is completely wrapped by the Al2O3 / Al composite material. This special structure has excellent mechanical and thermal properties.

[0055] Figure 2 A macroscopic image of the aluminum-based composite material having a porous Al2O3 / Al ceramic metal coating prepared in Example 1;

[0056] Figure 2 The results show that aluminum particles with uniform distribution and metallic luster appear on the coating surface ( Figure 2 The white bright spots in the middle) prove that the aluminum in the aluminum-based composite material fills the holes in the porous ceramic layer through high-temperature diffusion and diffuses into the coating surface.

[0057] Figure 3 The SEM image of the aluminum-based composite material with a porous Al2O3 / Al ceramic metal coating prepared in Example 1;

[0058] pass Figure 3It was found that the porous ceramic coating had been filled with molten aluminum (see the marked position) to form a ceramic-metal composite coating, which once again proved that we used a simple one-step method to prepare a ceramic-metal composite coating on the surface of an aluminum-based composite material.

[0059] Figure 4 XRD pattern of the aluminum-based composite material with porous Al2O3 / Al ceramic metal coating prepared in Example 1;

[0060] Figure 4 After scraping the surface of the coating, XRD characterization was performed and it was found that in addition to the diffraction peak of Al2O3, there were also a large number of Al diffraction peaks in the coating, proving that this technology can realize the preparation of ceramic-metal composite coatings.

[0061] Figure 5 Thermal conductivity data of aluminum-based composite materials with porous Al2O3 / Al ceramic metal coatings prepared in different embodiments.

[0062] from Figure 5 It can be seen that the aluminum-based composite material with porous Al2O3 / Al ceramic metal coating exhibits a high thermal conductivity of more than 100 W / mK.

[0063] Example 2: The difference between this example and Example 1 is that the concentration of sodium silicate in the electrolyte described in step 2 ① is 10 g / L, the concentration of sodium aluminate is 10 g / L, the concentration of sodium phosphate is 10 g / L, and the concentration of sodium hydroxide is 5 g / L; in step 2 ②, the pretreated substrate is immersed in a stainless steel electrolytic cell filled with an electrolyte, the pretreated substrate is connected to the positive electrode of the power supply, and the stainless steel electrolytic cell is connected to the negative electrode of the power supply, and the electrolyte temperature is 45°C, the applied voltage is 600V, the frequency is 600Hz and the proportion is 20%. Micro-arc oxidation was performed for 60 minutes under the condition of a void ratio of 6%, and an aluminum-based composite material with an alumina ceramic coating having a porous structure was obtained; in step 2②, the thickness of the alumina ceramic coating having a porous structure was 120 μm and the porosity was 39%; in step 3, the aluminum-based composite material with an alumina ceramic coating having a porous structure was placed in a high-temperature furnace, and the temperature was increased from room temperature to 650°C at a heating rate of 5°C / min, and the temperature was kept at 650°C for 30 minutes to obtain an aluminum-based composite material with a porous Al2O3 / Al ceramic metal coating. The other steps and parameters are the same as those in Example 1.

[0064] Example 3: The difference between this example and Example 1 is that the concentration of sodium silicate in the electrolyte described in step 2① is 20 g / L, the concentration of sodium aluminate is 5 g / L, the concentration of sodium phosphate is 30 g / L, and the concentration of sodium hydroxide is 10 g / L; in step 2②, the pretreated substrate is immersed in a stainless steel electrolytic cell filled with electrolyte, the pretreated substrate is connected to the positive electrode of the power supply, and the stainless steel electrolytic cell is connected to the negative electrode of the power supply, and the electrolyte temperature is 45°C, the applied voltage is 600V, the frequency is 600Hz and the proportion is 20%. Micro-arc oxidation was performed for 80 minutes under the condition of a void ratio of 20% to obtain an aluminum-based composite material with an alumina ceramic coating having a porous structure; in step 2②, the thickness of the alumina ceramic coating having a porous structure was 160 μm and the porosity was 42%; in step 3, the aluminum-based composite material with an alumina ceramic coating having a porous structure was placed in a high-temperature furnace, and the temperature was increased from room temperature to 630°C at a heating rate of 5°C / min, and the temperature was kept at 630°C for 30 minutes to obtain an aluminum-based composite material with a porous Al2O3 / Al ceramic metal coating. The other steps and parameters are the same as those in Example 1.

[0065] Figure 6 The friction coefficient of the aluminum-based composite material with porous Al2O3 / Al ceramic metal coating prepared in different embodiments.

[0066] Figure 7 Thermal expansion coefficient of aluminum-based composite materials with porous Al2O3 / Al ceramic metal coating prepared in different embodiments.

[0067] Figure 8 Room temperature compressive strength of aluminum-based composite materials with porous Al2O3 / Al ceramic metal coatings prepared in different embodiments.

[0068] Fig. 9 The fracture toughness of the aluminum-based composite material with a porous Al2O3 / Al ceramic metal coating prepared in different embodiments;

[0069] from Figure 6 to Figure 9 It can be seen that:

[0070] The aluminum-based composite material with porous Al2O3 / Al ceramic metal coating prepared in Example 1 exhibits a low friction coefficient of 0.35 and a thermal expansion coefficient of about 9.5×10 -6 / ℃, compression strength is 1.21GPa, fracture toughness is ~16.2MPa·m 1 / 2 .

[0071] The aluminum-based composite material with porous Al2O3 / Al ceramic metal coating prepared in Example 2 has a friction coefficient of <0.37, a thermal shock of 350°C for 500 times without damage, and a thermal expansion coefficient of 11.2×10-6 / ℃, room temperature compressive strength ~1.1GPa, fracture toughness ~16.8MPa·m 1 / 2 , thermal conductivity ≥100W / mK.

[0072] The aluminum-based composite material with porous Al2O3 / Al ceramic metal coating prepared in Example 3 has a friction coefficient of 0.42, a thermal shock of 400°C for 500 times without damage, and a thermal expansion coefficient of 12.3×10 -6 / ℃, room temperature compressive strength>1.02GPa, fracture toughness~17.1MPa·m 1 / 2 , thermal conductivity ≥100W / mK.

Claims

1. A method for preparing a porous Al2O3 / Al ceramic metal coating on the surface of an aluminum-based composite material, characterized in that The preparation method is specifically completed according to the following steps:

1. Pretreatment of the surface of aluminum-based composite materials: Removing impurities and oil stains on the surface of the aluminum-based composite material to obtain a pretreated substrate; 2. Preparation of porous micro-arc oxidation coating: ①, dissolving sodium silicate, sodium aluminate, sodium phosphate and sodium hydroxide in deionized water to obtain an electrolyte; ②, immersing the pretreated substrate into a stainless steel electrolytic cell filled with an electrolyte, connecting the pretreated substrate to the positive electrode of a power source, connecting the stainless steel electrolytic cell to the negative electrode of the power source, and micro-arc oxidation for a period of time under the conditions of an electrolyte temperature of 30°C to 50°C, an applied voltage of 400V to 600V, a frequency of 200Hz to 1000Hz, and a duty cycle of 4% to 30%, to obtain an aluminum-based composite material with an alumina ceramic coating having a porous structure; 3. Preparation of Al2O3 / Al ceramic coating with complete structure: The aluminum-based composite material with a porous alumina ceramic coating is placed in a high-temperature furnace, heated to 550°C-650°C, and kept at 550°C-650°C for a period of time to obtain an aluminum-based composite material with a porous Al2O3 / Al ceramic metal coating on the surface.

2. The method for preparing a porous Al2O3 / Al ceramic metal coating on the surface of an aluminum-based composite material according to claim 1, characterized in that The aluminum-based composite material described in step one is a SiC-reinforced aluminum alloy, wherein the mass fraction of SiC is 10% to 50%.

3. The method for preparing a porous Al2O3 / Al ceramic metal coating on the surface of an aluminum-based composite material according to claim 2, characterized in that The aluminum alloy described in step 1 is 2024 aluminum alloy, 6061 aluminum alloy, or 1050 aluminum alloy.

4. The method for preparing a porous Al2O3 / Al ceramic metal coating on the surface of an aluminum-based composite material according to claim 1, characterized in that The concentration of sodium silicate in the electrolyte described in step 2① is 1g / L~20g / L, the concentration of sodium aluminate is 1g / L~20g / L, the concentration of sodium phosphate is 1g / L~40g / L, and the concentration of sodium hydroxide is 1g / L~20g / L.

5. The method for preparing a porous Al2O3 / Al ceramic metal coating on the surface of an aluminum-based composite material according to claim 1, characterized in that The time of the micro-arc oxidation described in step 2② is 10min to 80min.

6. The method for preparing a porous Al2O3 / Al ceramic metal coating on the surface of an aluminum-based composite material according to claim 1, characterized in that In step 2②, the thickness of the porous alumina ceramic coating is 10 μm to 100 μm, and the porosity is 10% to 40%.

7. The method for preparing a porous Al2O3 / Al ceramic metal coating on the surface of an aluminum-based composite material according to claim 1, characterized in that The heating rate described in step 3 is 5°C / min to 8°C / min.

8. The method for preparing a porous Al2O3 / Al ceramic metal coating on the surface of an aluminum-based composite material according to claim 1, characterized in that The insulation time described in step 3 is 10 minutes to 30 minutes.

9. The method for preparing a porous Al2O3 / Al ceramic metal coating on the surface of an aluminum-based composite material according to claim 1, characterized in that In step three, the aluminum-based composite material with the alumina ceramic coating having a porous structure is placed in a high-temperature furnace, the temperature is raised to 600° C. to 650° C., and the temperature is kept at 600° C. to 650° C. for a period of time.

10. The method for preparing a porous Al2O3 / Al ceramic metal coating on the surface of an aluminum-based composite material according to claim 1, characterized in that The aluminum-based composite material with a porous Al2O3 / Al ceramic coating as described in step 3 has excellent mechanical properties and high thermal conductivity, excellent mechanical properties, a friction coefficient of <0.5, and the composite material remains intact after 500 thermal shocks at 400°C. The thermal expansion coefficient is 5 to 15×10 -6 / ℃, room temperature compression and bending strength>1GPa, fracture toughness about 16~20MPa·m 1 / 2 , thermal conductivity ≥100W / mK.

Citation Information

Patent Citations

  • Method for preparing low-solar-absorptivity and high-transmission-rate coating on magnesium alloy surface by means of micro-arc oxidation

    CN104532324A

  • Electrolyte for preparing micro-arc oxidation ceramic composite coating

    CN105780081A

  • Lightweight composite bulletproof plate and manufacturing method thereof

    CN107388899A

  • Preparation method of high-performance heat-conducting and insulating ceramic layer suitable for surface of aluminum substrate

    CN109267132A